2022
DOI: 10.1186/s12887-022-03300-7
|View full text |Cite|
|
Sign up to set email alerts
|

Establishing minimal clinically important difference for effectiveness of corrective exercises on craniovertebral and shoulder angles among students with forward head posture: a clinical trial study

Abstract: Background Previous studies have addressed the effects of different exercises and modalities on forward head posture (FHP), but the minimal clinically important difference (MCID) of the effect of exercises on FHP remains unclear. Therefore, this study aimed to investigate the effects of selective corrective exercises (SCEs) on the craniovertebral angle (CVA) and shoulder angle (SA) in students with FHP and to establish MCID for these angles. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Values below 48° are defined as FHP (Watson & Trott, 1993). Heydari et al found the minimal clinically important diference of CVA to be 1.40° (Heydari et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Values below 48° are defined as FHP (Watson & Trott, 1993). Heydari et al found the minimal clinically important diference of CVA to be 1.40° (Heydari et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…When utilizing photogrammetric methods to assess head posture, excellent intrarater (95% ICC of 0.98 to 0.99) and interrater (95% ICC, 0.91–0.99) reliabilities were reported [ 29 ]. A Nikon camera (D7500) was set on an adjustable camera stand at the height of every person's acromion with an 80 cm distance from them in lateral view [ 30 ]. Photos were taken by identifying the C7 vertebra of the neck, the ear tragus of the ear, and the head of the acromion bone in the shoulder using paper glue markers on individuals’ skin.…”
Section: Methodsmentioning
confidence: 99%
“…A cranial angle is formed by crossing two lines connecting the ear tragus with the C7 vertebrae and a horizontal line from the ear tragus. A shoulder angle is formed by intersecting two lines connecting the shoulder acromion with the C7 and a horizontal anterior–posterior line [ 30 ]. To examine the chest excursion, the diameter of the participant’s chest was measured using a tape meter at the level of the T10 spinous process in maximal exhalation and maximal inhalation phases.…”
Section: Methodsmentioning
confidence: 99%
“…Về bài tập thể dục tác động lên cơ như nghiên cứu trên đối tượng học sinh của tác giả Zahra Heydari cùng các cộng sự (n = 51) [8]. Nghiên cứu này có độ tuổi trung bình nhỏ hơn (11,8 ± 0,87), thời gian tập khoảng 30 phút trong mỗi buổi trong 8 tuần.…”
Section: đặC đIểm Chung Mẫu Nghiên Cứuunclassified